Gene action and heritability for photosynthetic activity in two wheat crosses - Simón, María Rosa (1994)
Gene action and heritability for photosynthetic activity were estimated from generation means in two wheat crosses during two stages (5; th; leaf and flag leaf between 2 and 5 days after anthesis). Six generations were available for each cross: parents (P₁ and P₂), F₁, F₂ and backcrosses (BC₁ and BC₂). Correlations between some morphophysiological characters and photosynthetic activity of the flag leaf was also determined. The joint scaling test described by Mather & Jinks was used to determine the gene action. It showed that them; [d]; [h]; [i], [l] (mean, additivity, dominance, additive x additive interallelic interaction effects, dominance x dominance interallelic interaction effects) model fits the two crosses at both measurement times. All the model genetic components were significant for the flag leaf, however for the 5; th; leaf only [h]; [i] and [l] were significant. The presence of additive and additive x additive effects suggested the possibility of selecting for this character using the flag leaf so as to obtain pure inbred lines. Dominance effects [h] were negative and dominance x dominance effects [l] were positive. Broad sense heritability values were medium to low. There were no correlations between the studied morphophysiological characters and the photosynthetic activity.